Assessment of Leishmaniasis notification system in Santiago del Estero, Argentina, 1990-1993. - Yadón, Z; Quigley, M; Davies, C; Rodrigues, L; Segura, E (2001)
Using a capture-recapture method, this study evaluates the completeness of the cutaneous leishmaniasis (CL) surveillance system in four districts of Santiago del Estero province, Argentina, for the period 1990-1993. Four reporting sources were evaluated: medical records kept by health facilities, interviews conducted during a case-control study, and the national and provincial levels of the leishmaniasis surveillance system (LSS). Using the capture-recapture method it was estimated that 210 cases (95% confidence interval [CI]: 202-218) of CL occurred in the four districts during the study period. Completeness of reporting to the leishmaniasis surveillance system at the national level was estimated to be 44.8% (95% CI: 43.2-46.4). The study results indicate that there is substantial underreporting within the LSS, although it did show the appropriate secular trends. The reasons for under-reporting and methods for addressing this problem are discussed.